Diplomacy of Constraint Revisited: Canada and the UN Korean Reconstruction Agency, 1950-55 - Donaghy, Greg (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
Historians remain divided over the nature of Canadian diplomacy during the Korean conflict of 1950-1953. Some favour traditional interpretations that stress Canadian-American differences over Western strategy in Cold War Asia, differences which encouraged Ottawa to pursue a “diplomacy of constraint.” Others minimize the gap between Ottawa and Washington, insisting that similar worldviews and shared Cold War interests severely limited Ottawa’s inclination and capacity to constrain the much more powerful United States. Canada’s experience with the United Nations Korean Reconstruction Agency (UNKRA), created in the fall of 1950 to help rebuild shattered South Korea, provides an opportunity to test these two interpretations against the still untapped documentary record. This paper explores the competing set of motives, goals, and preoccupations that shaped Canada’s approach to this UN agency. Humanitarianism and the allure of Asian trade were doubtless considerations. But politics trumped all. Support for the UN agency helped Ottawa sustain domestic backing, particularly among liberals and progressives, for the brutal Asian conflict. Canadian officials, like their UN and American counterparts, embraced UNKRA as a “pioneering” effort to showcase capitalist development in the context of the Asian Cold War. Most important, UNKRA was yet another multilateral mechanism available to Ottawa to offset, or constrain, the American tendency “to go it alone.”